PERBANDINGAN KONTAMINASI JAMUR Aspergillus sp PADA KACANG KEDELAI BERBIJI KUNING KUALITAS BAIK DAN JELEK YANG DIJUAL DI PASAR WIRADESA KAB. PEKALONGAN - Tuti Suparyati; Supriyo . (LPPM Universitas Pekalongan, 2014)
Soybean is one of the leguminous plants which became the manufacture of many foods that contain lots of high protein and vegetable oil, which allows the fungus to grow. Aspergillus sp is a fungus that can grow on soybeans, Aspergillus sp can cause infection include otomikosis, aspergillosis, and keratomikosis. Aspergillus sp can also secrete a toxin called aflatoxin, a known deadly and carcinogenic to humans and animals. Type descriptive research with cross sectional methode. The purpose of the study to compare the contamination of Aspergillus sp in yellow soybean seed of good or bad quality. The results showed, Aspergillus sp contamination in yellow soybean seed with poor quality as much as 8 samples (53.335%), contamination of Aspergillus sp in yellow soybean seed with good quality as much as 4 samples (26.67%). Conclusion Aspergillus sp more contamination in yellow soybean seed with better quality than the crappy quality It is advisable for consumers to be careful in choosing good foods that will be consumed. KEYWORDS : Aspergillus sp. and Soybeans